The Fungal Mycobiome and Its Interaction with Gut Bacteria in the Host - Qi Hui Sam (International Journal of Molecular Sciences, 2017)
The advent of sequencing technology has endowed us with the capacity to study microbes constituting the human commensal community that were previously non-culturable. Much of the initial works have concentrated on the bacterial flora constituting the gut microbiome, since specimens are readily accessible in health and disease. Less, however, is understood of the “silent population”—the fungal species, also known as the mycobiome. Living in symbiosis with bacteria as commensals in our body, it is perceivable that the mycobiome exerts an inadvertent influence on the microbiome. We review here the recent knowledge gained from study of the interaction between the mycobiome and microbiome in health and disease susceptibility, immunity, and consequences from antimicrobial treatment.